Reversal of epithelial-mesenchymal transition and inhibition of tumor stemness of breast cancer cells through advanced combined chemotherapy. (15th October 2022) - Cui, Yani; Zhao, Mingda; Yang, Yuedi; Xu, Ruiling; Tong, Lei; Liang, Jie; Zhang, Xingdong; Sun, Yong; Fan, Yujiang
Abstract: The abnormal activation of the Wnt/β-catenin signaling pathway and epithelial-mesenchymal transition (EMT) in drug-resistant tumor cells and cancer stem cells (CSCs) stimulate tumor metastasis and recurrence. Here, a promising combined chemotherapeutic strategy of salinomycin (SL) and doxorubicin (DOX) with specific inhibition of tumor stemness by a targeted co-delivery nanosystem was developed to overcome this abnormal progression. This strategy could be benefit drugs to effectively penetrate and infiltrate into spheres of 3D-cultured breast cancer stem cells (BCSCs). The expression of the Wnt/β-catenin signaling pathway-related genes ( β-catenin, LRP6, LEF1, and TCF12 ) and target genes ( Cyclin D1, Cmyc, and Fibronectin ) as well as CSC stemness-related genes ( Oct4, Nanog, and Hes1 ) was downregulated by redox-sensitive co-delivery micelles decorated with oligohyaluronic acid as the active targeting moiety. The changes in EMT-associated gene expression ( E-cadherin and Vimentin ) in vitro showed that the EMT process was also effectively inverted. This strategy achieved a strong inhibitory effect on solid tumor growth and an effective reduction in the risk of tumor metastasis in 4T1 tumor-bearing mice in vivo and effectively alleviated splenomegaly caused by the malignant tumor. Immunohistochemical staining analysis of E-cadherin, Vimentin, and β-catenin confirmed that the inversion of the EMT was also achieved in solid tumors. These results highlight the potential of SL and DOX combined chemotherapeutic strategy for eliminating breast carcinoma. Statement of significance: Cancer stem cells (CSCs), as an important part of tumor heterogeneity, can survive against conventional chemotherapy and initiate tumorigenesis, recurrence, and metastasis. Moreover, non-CSCs can convert into the CSC state through the abnormal Wnt/β-catenin pathway, which is closely related to the epithelial-mesenchymal transition (EMT) process. Here, redox-degradable binary drug-loaded micelles (PPH/DOX+SL) were designed to target CSCs and overcome drug resistance of breast cancer cells. The combined chemotherapy of salinomycin (SL) and doxorubicin (DOX) reversed drug resistance, while the PPH/DOX+SL micelles enhanced the intracellular accumulation and drug penetration of BCSC spheres. The introduction of SL downregulated the expression of tumor stemness genes and the Wnt/β-catenin pathway-related genes and inverted the EMT process. PPH/DOX+SL continuously inhibited tumor growth and invasion in vivo . Graphical abstract: Image, graphical abstract